Heat treatment behavior of Cr in the form of collagen powder and Al2O3 reinforced aluminum-based composite material - Shashi Prakash Dwivedi; Shubham Sharma; B.D.Y. Sunil; Nakul Gupta; Kuldeep K. Saxena; Sayed M. Eldin; Sana Shahab; Mohammed Ayad Alkhafaji; Sherzod Shukhratovich Abdullaev (Journal of Materials Research and Technology, 2023)
In the present study, collagen powder in the form of Cr has been extracted from chrome-containing leather waste. Extracted collagen powder along with alumina has been used as reinforcement with AA6061 matrix material. The composite material was fabricated by the stir casting technique. Comparative behavior of composite material with and without heat treatment was observed. The microstructure image of the Al/5% Al2O3/5% collagen composite has shown the uniform distribution of reinforcement particles. Proper wettability between the collagen powder, alumina, and matrix material was observed after the solidification for Al/5% Al2O3/5% collagen composite material. Tensile strength, hardness, ductility, and impact strength of composite material were significantly improved after the heat treatment process. However, results showed that ball-milled reinforced composite has a higher Young's modulus as compared to heat-treated composite. The percent porosity of aluminum alloy was found to be 0.18%. However, the porosity of Al/5% Al2O3/5% collagen powder ball milled composite material was found to be 1%. The XRD of the heat-treated Al/5% Al2O3/5% collagen powder composite showed the presence of Al, Al2O3, Cr, and Cr2O3 phases. Thermal expansion and corrosion behavior of the composite were also observed to identify the heat treatment effect on Al/Al2O3/collagen powder composite material.